Pengaruh Lingkungan Kerja, Insentif Dan Motivasi Kerja Terhadap Kinerja Karyawan PT. Liliyana Rama Jaya Di Kabupaten Gresik - Efendi Yusuf; Rois Arifin; Khalikussabir Khalikussabir (UNIVERSITAS ISLAM MALANG, 2021)
AbstractThis resarch aims to examine the effect of work environment, incentives and work motivation on employee performance at PT. Liliyana Rama Jaya in Gresik Regency. The population in this study were employees of PT. Liliyana Rama Jaya in Gresik Regency who works in all divisions such as skipper, operational staff and admin staff. The sampling technique used saturated sampling with a sample size of 42 respondents who worked at PT. Liliyana Rama Jaya in Gresik Regency in all divisions. The analytical method used is multiple linear regression analysis with IBM SPSS 25 application tools (statistical product and service solutions). Based on testing using the F test analysis, the results showed that there was a significant influence between the X variable (work environment, incentives and work motivation) simultaneously to the Y variable (Employee Performance) PT. Liliyana Rama Jaya in Gresik Regency. and t-test analysis of the research results showed that work environment variables significantly influence the performance of employees of PT. Liliyana Rama Jaya in Gresik Regency with a significance value of 0.013 <0.05, incentives have a significant effect on the performance of employees of PT. Liliyana Rama Jaya in Gresik Regency with a significance value of 0.018 <0.05, and work motivation has a significant effect on the performance of employees of PT. Liliyana Rama Jaya in Gresik Regency with a significance value of 0.024 <0.05. Keywords: Work Environment, Incentives, Work Motivation, and Employee Performance